Achieving Simultaneously Ultrahigh Brightness, Extremely Low Efficiency Roll‐Off and Ultralong Lifetime of Blue Fluorescent OLEDs by Using Donor–Acceptor‐Type 5, 9‐Diarylamine Functionalized Pyrenes. Issue 4 (11th December 2022) - Xie, Fuli; Yang, Xilin; Jin, Pengcheng; Wang, Xiao‐Tian; Ran, Huijuan; Zhang, Hailu; Sun, Huaming; Su, Shi‐Jian; Hu, Jian‐Yong
Abstract: In this study, four new donor–acceptor (DA)‐type blue emitters (Py(5, 9)BDPA, Py(5, 9)BMTBA, Py(5, 9)BDTBA, and Py (5, 9)BTTBA) are developed by adopting benzene ring as A units and the diphenylamine (DPA) with different electron‐donating substituents as D units connected to 1, 3‐positions and 5, 9‐positions of pyrene ring, respectively. Gratifyingly, single‐crystal X‐ray analysis of the compounds demonstrates that the disgusting excimers in solid‐state could be effectively inhibited by the D units even the unsubstituted DPA resorting to the superiority of introducing D‐units at the 5, 9‐positions of pyrene. The corresponding doped devices display ultrahigh luminance and extremely low efficiency roll‐off characteristics, especially for Py(5, 9)BDPA, a roll‐off of external quantum efficiency is less than 4.9% when the luminance is up to 30 000 cd m −2, also showing good operation stability of devices. The optimized advanced device of the representative blue emitter Py(5, 9)BDPA with a low manufacturing cost achieves extremely long LT95 (lifetime to 95% of the initial luminance) of 74 and 534 h at an initial luminance of 3000 and 1000 cd m −2, respectively. The ultralong lifetime of the emitter Py(5, 9)BDPA is eye‐catching in the reported blue OLED lifetime and further demonstrates the practical applications in display and lighting of these DA‐type pyrene‐based blue emitters. Abstract : Donor–acceptor‐type pyrene‐based fluorescent molecules realize highly efficient blue organic light‐emitting diodes with ultrahigh brightness ( L max : 48 280 cd m −2 ), extremely low efficiency roll‐off (current efficiency: 6.6% and external quantum efficiency: 4.9% at 30 000 cd m −2 ) and ultralong operational lifetime (LT95 : 534 and 33 732 h at an initial luminance of 1000 and 100 cd m −2 ).